Euthanasia: "medicine" of desire - Germán Zurriaráin, Roberto (2020)
When we think and talk about the end of human life, we ask ourselves: What would be better: euthanasia or the therapeutic obstinacy? Not one option, not another. We do not want to die prematurely, nor do we want to die intentionally. What we want is to die without suffering and in good condition. What cannot be admitted is that there are people who die without the chemical resources to alleviate their pain, without the social resources to look after themselves well, and without the affective resources to be accompanied with affection.Therefore, palliative care is the only ethical and sanitary option at the end of a person's life, in accordance with due respect for their dignity, and more, in a situation of vulnerability.On the contrary, to support euthanasia and therapeutic obstinacy is to defend, basically, a medicine of desire: two extremes of the same individualistic desire. To this is added, that euthanasia is understood in terms of a "right to die", which must be attended to.